(untitled) (Mongolian Journal of Humanities and Social Sciences, 2023)
As long as anímate and inanimate things exist, they inevitably contain information about the surrounding around them.With the help of this theory, it is believed that today neighboring countries have an opportunity to study the problems and questions in any field in more detail.Since the basic theoretical foundation is firmly established and the number of researchers who are interested in studying this is increasing year by year, let us introduce the general concept and integrated scheme of surrounding communication theory. Хураангуй: Амьтай ба амьгүй юмс оршин байгаа л бол түүнийг тойрсон орчны мэдээлэл зайлшгүй агуулагдаж байдаг. Тус онолоор дамжуулан хөрш улс орнууд аливаа нэг салбарт тулгамдаж буй асуудлыг илүү нарийвчлан судлах боломж бүрдэж байна гэж үзсэн. Онолын үндсэн суурь бэхжин тогтож жилээс жилд сонирхон судлах судлаачид нэмэгдэж байгаагийн хувьд орчны мэдээллийн онолын (ОМО) ерөнхий ойлголт, нэгдсэн бүдүүвчийг танилцуулж байна. Түлхүүр үг: Орчны мэдээллийн онол, хөрш улс, захын бүс нутаг, мэдээлэл